Adaptive traffic enforcement control mechanism for LANs interconnected by a high speed network. - Orozco-Barbosa, Luis
In this paper, a novel traffic enforcement control scheme is presented. The main aim of this scheme is to regulate the flow of traffic through a high speed backbone network interconnecting multiple LANs. The scheme is implemented at the interworking units where the traffic from each source destination LAN pair is monitored and enforced. This scheme aims to provide a fair sharing of the network resources. The interconnection of LANs through high speed backbone networks is of particular interest as the the deployment of this kind of system is seen as one of the most promising architecture to the development of the future Broadband-ISDN.
Keywords: Computer communication networks; Network protocols; Local networks; Performance evaluation